Representasi Pergerakan Perempuan dalam Buku Teks Sejarah SMA Kurikulum Merdeka - Handika Anggit Pramudya; Rikza Fauzan; Ana Nurhasanah (CV. ALIM'SPUBLISHING, 2026)
This study analyzes the representation of women in the national movement within high school history textbooks of the Merdeka Curriculum using the Discourse-Historical Approach (DHA) by Ruth Wodak. The findings reveal that women appear eight times less frequently than men, with their roles concentrated in education (30%), social organizations (25%), and health (20%), while political and military roles are minimal. Language analysis shows that active-strategic diction dominates descriptions of male figures (85%), whereas passive-emotional diction prevails for female figures (60-70%). The narrative structure applies the Great Men Theory, placing women as supplements to the main story. Visual representation marginalizes women through smaller photo sizes, peripheral placement, and domestic contexts. Ideological analysis confirms that patriarchal structures dominate all discourse production dimensions, with the state scoring 5/5 and women as subjects scoring only 1/5. The deconstruction score averages 2.2 out of 10, indicating a significant gap from the ideal inclusive representation. These findings demonstrate that despite the Merdeka Curriculum's inclusive aspirations, history textbooks continue to reproduce gender biases that marginalize women's historical contributions.